Lipid metabolism and exercise - Takeshi Hashimoto (Japanese Society of Physical Fitness and Sports Medicine, 2013)
The regulation of lipolysis in adipocytes involves coordinated actions of many lipid droplet (LD)-associated proteins such as perilipin, hormone sensitive lipase (HSL), adipose triglyceride lipase (ATGL), and its activator protein, CGI-58. Recently, the author and my colleagues described the cellular origin and physiological significance of micro LDs (mLDs) that emerge in the cytoplasm during active lipolysis, as well as the roles of key liplolytic proteins on mLDs in differentiated 3T3-L1 adipocytes. We suggested that, besides the surface of pre-existing central LDs, LD-associated proteins such as perilipin, CGI-58, HSL, and ATGL are actively involved in lipolysis on mLDs that are formed by FA re-esterification but probably devote to increasing total triacylglycerol (TAG) turnover and thus potentially net FA release. Thus, regulation of mLDs as well as LD-associated proteins may be an attractive therapeutic target against lipid-associated metabolic diseases. Physiological strategies such as exercise training aimed toward fat loss by active lipolysis in adipocytes (i.e. fat mobilization) and fatty acid (FA) oxidation in muscles (i.e. fat utilization) have become of preferred therapeutic agents against metabolic disorders. However, yet remarkably little is known about molecular mechanisms underlying augmented capacity of active lipolysis induced by exercise training, which should be elucidated in the future.